Cormac McCarthy's house : reading McCarthy without walls - Josyph, Peter (Southwestern Writers Collection series., 2013)
"Novelist Cormac McCarthy's brilliant and challenging work demands deep engagement from his readers. In Cormac McCarthy's House, author, painter, photographer, and actor-director Peter Josyph draws on a wide range of experience to pose provocative, unexpected questions about McCarthy's work, how it is achieved, and how it is interpreted. As a visual artist, Josyph wrestles with the challenge of rendering McCarthy's former home in El Paso as a symbol of a great writer's workshop. As an actor and filmmaker, he analyzes the high art of Tommy Lee Jones in The Sunset Limited and No Country for Old Men. Invoking the recent suicide of a troubled friend, he grapples with the issue of "our brother's keeper" in The Crossing and The Sunset Limited. But for Josyph, reading the finest prose-poet of our day is a project into which he invites many voices, and his investigations include a talk with Mark Morrow about photographing McCarthy while he was writing Blood Meridian; an in-depth conversation with director Tom Cornford on the challenges of staging The Sunset Limited and The Stonemason; a walk through the streets, waterfronts, and hidden haunts of Suttree with McCarthy scholar and Knoxville resident Wesley Morgan; insights from the cast of The Gardener's Son about a controversial scene in that film; actress Miriam Colon's perspective on portraying the Dueñ̃a Alfonsa opposite Matt Damon in All the Pretty Horses; and a harsh critique of Josyph's views on The Crossing by McCarthy scholar Marty Priola, which leads to a sometimes heated debate. Illustrated with thirty-one photographs, Josyph's unconventional journeys into the genius of Cormac McCarthy form a new, highly personal way of appreciating literary greatness."--Publisher's website.